2020
DOI: 10.3390/mi11080715
|View full text |Cite
|
Sign up to set email alerts
|

Particle Swarm Optimization Algorithm-Based Design Method for Ultrasonic Transducers

Abstract: In order to improve the fabrication efficiency and performance of an ultrasonic transducer (UT), a particle swarm optimization (PSO) algorithm-based design method was established and combined with an electrically equivalent circuit model. The relationship between the design and performance parameters of the UT is described by an electrically equivalent circuit model. Optimality criteria were established according to the desired performance; then, the design parameters were iteratively optimized using a PSO alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Then, the design parameters of a concave annular high intensity focused ultrasonic transducer could be optimized by using a nonlinear programming algorithm, which was beneficial for fabricating a high-intensity focused ultrasonic transducer. By combining an ECM and the particle swarm optimization (PSO) algorithm, Chen et al [ 49 ] developed an optimization design method for PUT (as shown in Figure 7 C). According to the optimized design parameters, the fabricated PUT had a CF of 6.3 MHz and a −6 dB bandwidth of 68.25%.…”
Section: Efficient Optimization Design Methods For a Putmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the design parameters of a concave annular high intensity focused ultrasonic transducer could be optimized by using a nonlinear programming algorithm, which was beneficial for fabricating a high-intensity focused ultrasonic transducer. By combining an ECM and the particle swarm optimization (PSO) algorithm, Chen et al [ 49 ] developed an optimization design method for PUT (as shown in Figure 7 C). According to the optimized design parameters, the fabricated PUT had a CF of 6.3 MHz and a −6 dB bandwidth of 68.25%.…”
Section: Efficient Optimization Design Methods For a Putmentioning
confidence: 99%
“… ( A ) Evolutionary algorithm-based optimization design method for a piezoelectric ultrasonic transducer (reproduced from [ 47 ]); ( B ) mathematical model for a concave annular high intensity focused ultrasonic transducer and its finite element model (reproduced from [ 47 ]); ( C ) optimization design for a piezoelectric ultrasonic transducer using the particle swarm optimization algorithm (reproduced from [ 48 ]); ( D ) functionally graded piezoelectric ultrasonic transducer optimized by using the topological optimization algorithm (reproduced from [ 49 ]). …”
Section: Figurementioning
confidence: 99%
“…Particle swarm optimization (PSO) is a widely used swarm-intelligence-based optimization method [ 18 , 19 , 20 , 21 , 22 ]. However, a major drawback of PSO is that it tends to get trapped in local optima and is, therefore, unable to find a global optimal solution.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on enhancement of the control performance, optimization techniques have been widely used and applied. They provide systematic procedure for designing of controllers, tuning the parameters and gains, and online estimation/calibration for unknown parameters caused by environmental changes or disturbances [21,28]. In the literature, various optimization algorithms have been developed to improve the quality of the closed-loop system such as Artificial Bee Colony (ABC) algorithm [29], Ant Colony Optimization (ACO) algorithm [30], Bacterial Foraging Optimization (BFO) algorithm [31], Multi-Verse Optimization (MVO) algorithm [32] and Gravitational Search Algorithm (GSA) [33].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, various optimization algorithms have been developed to improve the quality of the closed-loop system such as Artificial Bee Colony (ABC) algorithm [29], Ant Colony Optimization (ACO) algorithm [30], Bacterial Foraging Optimization (BFO) algorithm [31], Multi-Verse Optimization (MVO) algorithm [32] and Gravitational Search Algorithm (GSA) [33]. Particle Swarm Optimization (PSO) is one of the effective optimization methods that has been successfully used in tuning PID controllers as in [34], for quadrotor stabilization based on integral backstepping control design [35], for tuning the parameters of fuzzy PD controller with minimization of integral square error cost function in [36], to improve the performance of an ultrasonic transducer [28]. For the control of DP systems, authors in [21] have deployed the PSO method to optimize the fuzzy function/parameters to enhance the quality and performance of the DP system of the ship.…”
Section: Introductionmentioning
confidence: 99%